2008
DOI: 10.1007/s00404-007-0503-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower genital tract rhabdomyosarcoma: case series and literature review

Abstract: Most patients present with vaginal bleeding and a palpable cervical or vaginal mass. While the optimal management of these tumors is uncertain, primary therapy with wide local excision and chemotherapy can result in prolonged survival and cure in patients with early stage RMS. Vaginal lesions have a better prognosis than cervical lesions. In patients with un-embrional RMS, large size of lesion, cervical origin and extent of disease, survival rates was decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 11 publications
0
29
0
6
Order By: Relevance
“…The mean age at diagnosis of patients with cervical lesion is higher than that of patients with vaginal lesions . Primary vaginal lesions are more common than cervical lesions [4]. We report a case of sarcoma botryoides of the cervix presenting as a cervical polyp in 20 year old female.…”
mentioning
confidence: 91%
“…The mean age at diagnosis of patients with cervical lesion is higher than that of patients with vaginal lesions . Primary vaginal lesions are more common than cervical lesions [4]. We report a case of sarcoma botryoides of the cervix presenting as a cervical polyp in 20 year old female.…”
mentioning
confidence: 91%
“…2 Vaginal primaries are five times more common than cervical primaries. 3 The mean age at diagnosis of patients with ERMS arising in the cervix is higher than of patients with vaginal lesions. Although ERMS has been described in females as young as 5 months of age, it tends to appear in an older age group (children or even young adults) than those occurring in the vagina.…”
Section: Introductionmentioning
confidence: 99%
“…Although ERMS has been described in females as young as 5 months of age, it tends to appear in an older age group (children or even young adults) than those occurring in the vagina. 1,3 The Intergroup Rhabdomyosarcoma Study Group (IRSG) has reported a new classification of ERMS distinguishing three major histological subtypes: embryonal, alveolar and undifferentiated. The embryonal subtype is the most common, accounting for 68% of all ERMS cases, with classic, botryoid and spindle cell variants embracing 49, 6 and 3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RMS is rare in adults, with soft-tissue sarcomas making up less than 1% of malignancies in adults and RMS accounting for 3% of all soft-tissue sarcomas. In University of Tehran data only 6 RMS were found (0.39%) among the 1,528 patients with genital tract malignancies [1]. In Korea, a total of 8 cases of RMS were reported in young adults but there has been no case in which the patient was older than 40 years.…”
mentioning
confidence: 98%